Problemy selekcji i ważenia zmiennych w zagadnieniu klasyfikacji - Walesiak, Marek (Variable Selection and Weighting Problems in Cluster Analysis, 2005)
Choice of variables is the one of the most important steps in a cluster analysis. Variables used in applied clustering should be selected and weighted carefully. In cluster analysis we should include only those variables that are believed to help discriminate the data.In article:- main aspects of selection and weighting of variables to cluster were characterised,- point at limitations of variable selection for cluster analysis based on data generated from normal distribution,- main approaches to variable selection and weighting for cluster analysis were discussed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 106-118